(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Environmental issues have, recently generated much interest among scholars or academics, administrators, politicians, students and environmentalists. But in the proper context or global environmental debate, it has become continuously difficult to separate the interrelationship between man, environmental resources and conservation measures. The study employs systematic sampling techniques in selecting the respondents for the interview. The selection was based on the settlement arrangement pattern in the study site as sampling frame. The structured questionnaires were administered to the respondents with aid of research assistant for proper interpretation of the questionnaire to local language (Bade). Cereals crop production especially millet thrive well due to its physiological ability to withstand adverse environment conditions. The study also finds that the protected areas is suitable for rice production. Several species of wild plants were exploited either for construction, income, medicinal purposes, fuel wood, and fodder. Grazing is another activity taking place in the study site due the availability of green pasture